TERT Mutation Is Accompanied by Neutrophil Infiltration and Contributes to Poor Survival in Isocitrate Dehydrogenase Wild-Type Glioma - Gao, Mengqi; Lin, Yi; Liu, Xing; Zhao, Zheng; Zhu, Zhiyuan; Zhang, Hongbo; Ban, Yunchao; Bie, Yanan; He, Xiaozheng; Sun, Xiang; Zhang, Shizhong (Frontiers in Cell and Developmental Biology, 2021)
Mutation of the telomerase reverse transcriptase (TERT) promoter has been demonstrated as an unfavorable prognostic marker in patients with isocitrate dehydrogenase wild-type (IDHwt) glioma. This study aimed to investigate the immune role of TERT promoter mutation status which could improve prognostic prediction in IDHwt. TERT mutation status, IDH mutation, and 1p-19q codeletion status data were obtained from 614 glioma cases from the Cancer Genome Atlas, and 325 cases from the Chinese Glioma Genome Atlas. The same information was obtained from 49 clinical glioma tissues. TERT mutation is preferentially present in glioblastoma and IDH-wt gliomas and is associated with poor prognosis. Moreover, TERT mutation was associated with infiltration of neutrophils and expression of neutrophil chemokines. which might partially contribute to the poor outcome in IDH-wt glioma. Furthermore, patients with IDH-wt glioma did not harbor increased peripheral neutrophils, implying that the infiltrated neutrophil in the tumor environment might due to cytokine chemotaxis. In this study, we hereby propose that TERT mutation might be a molecular driver of the dysfunctional immune microenvironment in IDH-wt glioma. TERT mutation may be a potential immune therapeutic target for optimizing treatment combinations and patient selection for glioma immunotherapy.